Evaluation of quality of life and burden of caregivers of adolescents with autism spectrum disorder in Recife, State of Pernambuco, Brazil (Research, Society and Development, 2020)
The aim of this study was to assess the quality of life and burden of caregivers of adolescents aged 10 to 19 years with autism spectrum disorder, enrolled in state and private public schools in Recife. Cross-sectional study with a sample of 57 caregivers (44 in the state public school and 13 in the private one). Data were collected using the instruments: The World Health Organization for Quality of Life (short version) in the assessment of quality of life and the Zarit Burden Interview Scale to assess the burden. The statistical program Statistical Package for Social Science, version 17.0, was used for analysis, with a significance level of p